Beauvericin inhibits melanogenesis by regulating cAMP/PKA/CREB and LXR-α/p38 MAPK–mediated pathways. Issue 1 (December 2018) - Lee, Seung; Park, See-Hyoung; Oh, Sae; Yoo, Ju; Kwon, Kitae; Park, Se; Kim, Jangsoon; Lee, Hak; Cho, Jae; Lee, Jongsung
Abstract Melanogenesis is the process of production of melanin pigments that are responsible for the colors of skin, eye, and hair and provide protection from ultraviolet radiation. However, excessive levels of melanin formation cause hyperpigmentation disorders such as freckles, melasma, and age spots. Liver X receptors (LXR) are nuclear oxysterol receptors belonging to the family of ligand-activated transcription factors and physiological regulators of lipid and cholesterol metabolism. In the skin, activation of LXRs stimulates differentiation of keratinocytes and augments lipid synthesis in sebocytes. However, the function of LXRs in melanogenesis has not been clearly elucidated. In addition, although beauvericin, a well-known mycotoxin primarily isolated from several fungi, has various biological properties, its involvement in melanogenesis has not been reported. Therefore, in this study, we examined the effects of beauvericin on melanogenesis and its molecular mechanisms. Beauvericin decreased melanin content and tyrosinase activity without any cytotoxicity. Beauvericin also reduced protein levels of MITF, tyrosinase, TRP1, and TRP2. In addition, beauvericin suppressed cAMP-PKA-CREB signaling and upregulated expression of LXR-α, resulting in the suppression of p38 MAPK. Our results indicate that beauvericin attenuates melanogenesis by regulating both cAMP/PKA/CREB and LXR-α/p38 MAPK pathways, consequently leading to a reduction of melanin levels.